Analisis Faktor Prokrastinasi Akademik Mahasiswa saat Pembelajaran Jarak Jauh pada Mahasiswa di Pendidikan Islam - Supriadi Supriadi (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
Distance Learning (Online) in students affects the tendency to delay or not complete an assignment. In this case, it is undoubtedly a sign of procrastination. Procrastination is generally completing a task when the deadline is near or near the collection deadline. This will result in people who procrastinate feeling scattered. These feelings can result in students completing assignments carelessly and, in a hurry, impacting academic untruths. In this case, this study aims to describe the factors of student academic procrastination during distance learning (online). The research method uses qualitative research focusing on library research where the references used are the results of previous studies in journals, books, and other sources. From this research, it can be concluded that the analysis of factors that can influence academic procrastination in students includes factors related to the characteristics that surround: negative self-image, factors related to individual capabilities, empathy factors, psychological factors, and Impression factors on the personality of the task.